The antimalarial artemisinin is a non-electrophilic agonist of the transient receptor potential ankyrin type 1 receptor-channel - Huţanu, Debora Elena; Oprita, George; Domocos, Dan; Selescu, Tudor; Manolache, Alexandra; Stratulat, Teodora; Sauer, Susanne; Tunaru, Sorin; Babes, Alexandru; Babes, Ramona Madalina (European Journal of Pharmacology, 2023)
Artemisinin and its derivatives are the main therapeutic drugs against Plasmodium protists, the causative agents of malaria. While several putative mechanisms of action have been proposed, the precise molecular targets of these compounds have not been fully elucidated. In addition to their antimalarial properties, artemisinins have been reported to act as anti-tumour agents and certain antinociceptive effects have also been proposed. We investigated the effect of the parent compound, artemisinin, on a number of temperature-gated Transient Receptor Potential ion channels (so called thermoTRPs), given their demonstrated roles in pain-sensing and cancer. We report that artemisinin acts as an agonist of the Transient Receptor Potential Ankyrin type 1 (TRPA1) receptor channel. Artemisinin was able to evoke calcium transients in HEK293T cells expressing recombinant human TRPA1, as well as in a subpopulation of mouse dorsal root ganglion (DRG) neurons which also responded to the selective TRPA1 agonist allyl isothiocyanate (AITC) and these responses were reversibly abolished by the selective TRPA1 antagonist A967079. Artemisinin also triggered whole-cell currents in HEK293T cells transiently transfected with human TRPA1, as well as in TRPA1-expressing DRG neurons, and these currents were inhibited by A967079. Interestingly, using human TRPA1 mutants, we demonstrate that artemisinin acts as a non-electrophilic agonist of TRPA1, activating the channel in a similar manner to carvacrol and menthol. These results may provide a better understanding of the biological actions of the very important antimalarial and anti-tumour agent artemisinin.
CRIS-Team Scopus Importer:2023-01-13
Keywords: Antimalarial; Artemisinins; Electrophilic; thermoTRP channels; TRPA1